Discovery of new methylation markers to improve screening for cervical intraepithelial neoplasia grade 2/3. Issue 1 (December 2016) - Boers, A.; Wang, R.; van Leeuwen, R.; Klip, H.; de Bock, G.; Hollema, H.; van Criekinge, W.; de Meyer, T.; Denil, S.; van der Zee, A.; Schuuring, E.; Wisman, G.
Abstract Background Assessment of DNA promoter methylation markers in cervical scrapings for the detection of cervical intraepithelial neoplasia (CIN) and cervical cancer is feasible, but finding methylation markers with both high sensitivity as well as high specificity remains a challenge. In this study, we aimed to identify new methylation markers for the detection of high-grade CIN (CIN2/3 or worse, CIN2+) by using innovative genome-wide methylation analysis (MethylCap-seq). We focused on diagnostic performance of methylation markers with high sensitivity and high specificity considering any methylation level as positive. Results MethylCap-seq of normal cervices and CIN2/3 revealed 176 differentially methylated regions (DMRs) comprising 164 genes. After verification and validation of the 15 best discriminating genes with methylation-specific PCR (MSP), 9 genes showed significant differential methylation in an independent cohort of normal cervices versus CIN2/3 lesions (p  < 0.05). For further diagnostic evaluation, these 9 markers were tested with quantitative MSP (QMSP) in cervical scrapings from 2 cohorts: (1) cervical carcinoma versus healthy controls and (2) patients referred from population-based screening with an abnormal Pap smear in whom also HPV status was determined. Methylation levels of 8/9 genes were significantly higher in carcinoma compared to normal scrapings. For all 8 genes, methylation levels increased with the severity of the underlying histological lesion in scrapings from patients referred with an abnormal Pap smear. In addition, the diagnostic performance was investigated, using these 8 new genes and 4 genes (previously identified by our group:C13ORF18, JAM3, EPB41L3, andTERT ). In a triage setting (after a positive Pap smear), sensitivity for CIN2+ of the best combination of genes (C13ORF18 /JAM3 /ANKRD18CP) (74 %) was comparable to hrHPV testing (79 %), while specificity was significantly higher (76 % versus 42 %, p  ≤ 0.05). In addition, in hrHPV-positive scrapings, sensitivity and specificity for CIN2+ of this best-performing combination was comparable to the population referred with abnormal Pap smear. Conclusions We identified new CIN2/3-specific methylation markers using genome-wide DNA methylation analysis. The diagnostic performance of our new methylation panel shows higher specificity, which should result in prevention of unnecessary colposcopies for women referred with abnormal cytology. In addition, these newly found markers might be applied as a triage test in hrHPV-positive women from population-based screening. The next step before implementation in primary screening programs will be validation in population-based cohorts.